AN ANALYSIS OF TRANSLATION SHIFTS OF PHRASAL VERB IN FAMILY ALBUM AND IT'S TRANSLATION ALBUM KELUARGA - SARI , NOVI HAYU TRIANA (2007)
This research studies about the translation shift of phrasal verb on Danielle Steel's novel family album and its translation Album Keluarga. The object of the research is phrasal verbs on the novel and its translation. In collecting data, the writer uses documentation method and technique of coding. The research describes the kinds of translation shift of phrasal verb and appropriateness of translation. To achieve these objectives, she classifies the data based on the type of phrasal verb and then she applies the appropriateness of translation. The result of the data analysis shows that from 145 data, the writer finds five types of phrasal verb. They are (1) intransitive (with no object), (2) transitive verbs whose object can come in two positions after the verb or after the particle, (3) transitive verbs whose object must come between the verb and the particle, (4) transitive verbs whose object must come after the particle, and (5) verbs with two objects, one after the verb, the other after the particle. The phrasal verb can be translated into verb, noun, adjective, and adverb in Indonesian based on the translation the researcher finds the type of phrasal verb and its translation shift from English to Indonesian. According the data, the researcher finds the type of phrasal verb and translation shifts, they are; firstly, intransitive phrasal verb is translated into verb that has 18 data or 12,41%, intransitive phrasal verb is translated into noun that has 2 data or 4,14%, and intransitive phrasal verb is translated into adjective that has 1 data or 0,69%. Secondly, intransitive phrasal verb is translated into verb that has 19 data or 13%. Thirdly, intransitive phrasal verb is translated into verb that has 5 data or 3,4%. Fourthly, intransitive phrasal verb is translated into verb that has 92 or 63,45%, intransitive phrasal verb is translated into adverb that has 2 data or 1,38%. Finally, intransitive phrasal verb is translated into verb that has 2 data or 1,38%. Related to the second problems, based on the data from 145 data, there are 144 data or 99,33% appropriate translation and only one data or 0,69% that is inappropriate translation. It means that translation of Family Album novel belongs to good translation.